Speaking Anxiety Symptoms among Tenth-Grade Students in English Language Classes - Masitowarni Siregar; Rahmad Husein; Ayunda Wulandari; Asrita Sari; Nurur Risky Aulia (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2025)
This study investigates the prevalence and nature of speaking anxiety among tenth-grade students at SMAN 15 Medan, with a particular focus on physical, mental, and emotional symptoms. Employing a descriptive qualitative design, the research utilized observations and interviews to capture a comprehensive picture of the students' anxiety experiences. Analysis of the data revealed that physical symptoms were the most frequently reported, with a total of 83 instances documented. These included rapid heartbeat, difficulty speaking, trembling, and difficulty breathing, among others. Emotional symptoms were also prominent, with students frequently expressing feelings of nervousness, fear, and embarrassment. Mental symptoms, while less common, included issues such as memory lapses and cognitive disruptions. The findings indicate that speaking anxiety manifests predominantly through physical and emotional symptoms, with mental symptoms being less frequent but still impactful. Additionally, many students exhibited multiple types of symptoms simultaneously, underscoring the multifaceted nature of speaking anxiety. This research highlights the need for a holistic approach to addressing speaking anxiety, suggesting that future interventions should focus on reducing physical symptoms, enhancing emotional support, and improving cognitive strategies to help students manage their speaking anxiety effectively.